Microscopical descriptions and chemical analysis by HPTLC of Taraxacum officinale in comparison to Hypochaeris radicata: a solution for mis-identification (2014)
ABSTRACT: Taraxacum officinale F. H. Wigg, Asteraceae, is frequently misidentified or substituted with Hypochaeris radicata L., Asteraceae (false dandelion). To increase our knowledge of T. officinale and differentiate it from H. radicata, we investigated the two species using a combination of taxonomy, microscopy, and chromatographic studies via fingerprint profiles. Micromorphological characteristics were studied using scanning electron microscopy, while optic light microscopy was used for histochemical observations. Fingerprint profiles were constructed using HPTLC. T. officinale was found to have a morphologically distinct type of pluricellular trichomes that can be used to differentiate the two species, as these structures were not identified in H. radicata samples. Furthermore, two types of laticiferous vessels may also be distinctive characteristics of T. officinale at species level. In addition, the HPTLC data derived from methanolic extracts of H. radicata and T. officinale roots showed clearly different chemical profiles. Thus this study establishes the authenticity of T. officinale, and the observed parameters could help minimize drug substitutions in herbal medicines.